The Effect of Nutritional Counseling with Booklet Media on Food Waste in Hypertension Patients at Praya Regional Hospital - Baiq Asmarani Candra Dewi; Luh Suranadi; Made Darawati; Reni Sofiyatin; I Gde Narda Widiada (Poltekkes Kemenkes Mataram, 2024)
Background: Food waste indicates the success of nutrition services in hospitals; food waste exceeding 20% indicates failure in food management. Nutrition counseling plays a vital role in providing knowledge, attitudes, and behaviors regarding diet so that it can reduce food waste. High Blood Pressure (hypertension) is an increase in blood pressure in the arteries. The number of hypertensive patients at Praya Regional Hospital in November 2022 will be around 630.Objective: This research aimed to determine the effect of nutritional counseling using booklet media on food waste in hypertensive patients at Praya Regional Hospital Research Methods: This research design is quasi-experimental, using a non-randomized control group pre-and post-test. Sampling was carried out using purposive sampling, with 22 samples, 11 for the treatment group and 11 for the control group. Data analysis used the Mann-Whitney U test. Counseling is carried out using a face-to-face lecture method using booklet media. The research was conducted for one month at Praya Regional Hospital. Research Result: The study's results showed a difference in patient food waste (staple food, vegetable side dishes, animal side dishes, and vegetables) before and after nutritional counseling. Still, the difference was not statistically significant (p-value = >0.05). Changes in food waste do not significantly affect staple foods, animal side dishes, vegetable side dishes, and vegetables. Conclusion: Nutritional counseling using booklet media does not affect food waste in hypertensive patients at Praya Regional Hospital.